Outcome of Minimally Invasive Percutaneous Plate Osteosynthesis Using Locking Compression Plate for Distal Tibial Fractures - Rampure, Sagar; Choraria, Harsh; Hanchate, Krishna; Mahadik, Sujay K; Deshpande, Shrikant (International Journal of Integrated Health Sciences, 2024)
Objectives: To assess the functional and radiological outcomes of the distal tibia fractures managed surgically with a locking compression plate by MIPPO technique.Methods: This prospective observational study included 34 patients with distal tibial fractures treated at Bharati Vidyapeeth (Deemed to be University) Medical College and Hospital, Sangli, India. After ethics committee approval and informed consent, eligible adults with complex or unfavorable simple, closed fractures were enrolled. Exclusions were patients under 18 with pathological fractures or comorbidities affecting functional outcomes. Standard preoperative protocols and imaging were conducted. All patients were surgically managed with a locking compression plate by MIPPO technique. Postoperatively, exercises and staged weight-bearing were implemented. Follow-up assessments at 45, 90, 135, and 180 days evaluated pain, movement, and radiological union using Olerud and Molander score. Statistical analysis utilized paired t-test and Chi-Square test.Results: Out of 34 patients with distal tibial fractures, 24 (70.6%) were males and 10 (29.4%) were females with a mean age of 41.88 years. Most fractures were 42A1 (35.3%) and 43A2 (32.4%). Post-operative superficial wound infection occurred in 3 (8.8%) and deep infection in 2 (5.9%). Mean union time was 16.62 weeks. Functional outcomes were excellent in 3 (8.8%), good in 22 (64.7%), and fair in 9 (26.5%). At six months, complications included ankle stiffness (29.4%), non-union (20.6%), and malunion (8.8%). No cases had plate or screw breakage.Conclusion: MIPPO technique allows for good functional outcomes while reducing complications, especially in fractures with poor soft tissue conditions.